La prosa de Sigüenza y Góngora y la formación de la conciencia criolla mexicana - Lorente Medina, Antonio (Lengua y estudios literarios, 1996)
"Well-documented and methodical study is divided into five parts: Theatro de Virtudes Políticas, Libra Astronómica y Philosóphica, Parayso Occidental, Piedad heroyca de Don Fernando Cortés, and historical chronicles that Sigüenza authored including Infortunios de Alonso Ramírez and Mercurio Volante. Analyzes sources, form, and content of the works. Noteworthy final chapter focuses on the ideological and cultural implications of Sigüenza's works. Of interest to scholars and students"--Handbook of Latin American Studies, v. 58.. - http://www.loc.gov/hlas/